EVALUASI PELAKSANAAN REKLAMASI LAHAN PENAMBANGAN BIJIH NIKEL PT. WIJAYA INTI NUSANTARA DI KECAMATAN LAEYA, KONAWE SELATAN - Kamrullah M Kamrullah M; M. Tufaila Hemon; Hasbullah Syaf (Jurnal Perencanaan Wilayah, 2019)
This research aims to know the : (1) Implementation of land use, erosion and sedimentationcontrol, revegetation, maintenance and placement of reclamation guarantees based on ForestryMinister's Regulation Number P.60/Menhut-II /2009 about Guidelines for Assessing the Success ofForest Reclamation and Decree of the Minister of Energy and Mineral Resources Number 1827K/30/MEM/2018 about Guidelines for the Implementation of the Principle of Good MiningTechnique; (2) The Suitability of the implementation of the reclamation of the PT. WIN with the planthe pattern space RTRW South Konawe Regency. The research method used is field survey and imageinterpretation with variables namely (1) Implementation of land use, (2) Erosion and sedimentationcontrol, and (3) Revegetation. The research results showed that value the level of success ofreclamation in PT. WIN according Forestry Minister's Regulation Number P.60/Menhut-II/2009 was73,8 with medium category it means reclamation acceptable but still necessary repairs whileaccording to the Decree of the Minister of Energy and Mineral Resources Number 1827K/30/MEM/2018 is 79.04%. The results of the analysis of spatial pattern of space RTRW SouthKonawe Regency with land reclamation PT. WIN is the agricultural utilization of food crop acreagedry land (Moor) and the results of the analysis of the reclamation plan cost calculation of PT. WIN forthe second period of 2015 - 2019 covering an area of 8.58 hectares required Rp. 3,291,882,543, whilethose planned by PT. WIN Rp. 1,980,932,611, -.Keywords: Reclamation, Spatial Patterns, Reclamation Costs